Implementasi Keamanan Chat Realtime Menggunakan Aes-Cbc Dan Base64 - Firdaus Alfajar Sudarsih; Akbar Mutaqin (Journal of Information System and Artificial Intelligence, 2021)
this journal presents an encryption process and description using AES-CBC and Base64, in this study perform several processes such as problem analysis, system design using UML, coding process, testing, and data collection process. To get results from this study will be done the encryption process and text description 30 times that will use different keys and initial vectors to test messages that are already encrypted according to the initial text when in the description. From the research, it can be concluded that the results show that 57% of the messages encrypted have similarities to the contents of the original message, because they use the same key and initial vector to decrypt and, that 43% of the messages that are decrypted have no similarities to the contents of the original message. because they use different key and initial vector to decrypt.